The Influence of Work Motivation and Work Discipline on Employee Performance Mediated by Organizational Commitment at Teungku Fakinah General Hospital Banda Aceh City - Fakhrurrazi, Fakhrurrazi; Isa Indrawan, Muhammad (Lafadz Jaya Publisher, 2023)
This study aims to see the effect of Work Motivation and Work Discipline on Employee Performance and Organizational Commitment by carrying out research requirements in order to obtain research results in the form of research methods including using associative quantitative research types, this research was conducted at Teungku Fakinah General Hospital, Banda Aceh City, the population was 141 employees and reduced to 104 samples using the slovin technique, data collection techniques were carried out by distributing questionnaires and surveys. The research model used is Path Analysis using research measuring tool in the form of the Smart PLS Version 3.3.3 application. Based on the results of the research that has been done and data analysis as explained in the previous chapter, the following conclusions are conveyed from the results of the research as follows: Work Discipline has a not significant positive effect on Employee Performance. The results can be seen in the Path Coefficients table with an Orginal Sample of 0.298 and P values 0.154 > 0.05 Work Discipline has a positive and significant effect on Employee Organizational Commitment. The results can be seen in the Path Coefficients table with an Original Sample of 0.632 Pvalues 0.000 <0.05. Organizational Commitment has a positive and significant effect on Employee Performance Employee results can be seen in the Path Coefficients table with an Original Sample of 0.614 and P values 0.001 <0.05. Work Motivation has no significant negative effect on Employee Performance. The results can be seen in the Path Coefficients table with an Original Sample of -0.116 and P values of 0.542. Work Motivation has a positive and significant effect on Organizational Commitment. The results can be seen in the Path Coefficients table with an Original Sample of 0.309 P values 0.000 <0.05. Organizational Commitment is able to become an intervening variable and has a positive and significant indirect effect on Work Discipline and Employee Performance. The results can be seen in the Path Coefficients table with an Orginal Sample of 0.388 and P values of 0.002 <0.05. Organizational Commitment is able to become an intervening variable and has a positive and significant indirect effect on Work Motivation and Employee Performance. The results can be seen in the Path Coefficients table with an Original Sample of 0.190 and P values of 0.040 <0.05.